2001
DOI: 10.1051/0004-6361:20010479
|View full text |Cite
|
Sign up to set email alerts
|

Pulsational constraints to the metallicity gradient in the Galactic disk

Abstract: Abstract. BVI data of Galactic Cepheids observed in the solar neighborhood and in the outer disk are analyzed on the basis of nonlinear, non-local and time-dependent convective pulsating models computed for different assumptions on the chemical composition. We show that the theoretical color-color, period-luminosity, and period-luminosity-color relations, as predicted by the models with varying metal content, provide the way to simultaneously estimate the true distance modulus µ0 and the metal content Z of eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
36
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 22 publications
9
36
1
Order By: Relevance
“…Data on cepheid variables should in principle agree with the B star results, which is confirmed by a recent analysis by Caputo et al (2001), but a flatter gradient and/or a discontinuity around 10 kpc is suggested from the high resolution data by Andrievsky et al (2002).…”
Section: Abundance Gradients From Pnsupporting
confidence: 80%
“…Data on cepheid variables should in principle agree with the B star results, which is confirmed by a recent analysis by Caputo et al (2001), but a flatter gradient and/or a discontinuity around 10 kpc is suggested from the high resolution data by Andrievsky et al (2002).…”
Section: Abundance Gradients From Pnsupporting
confidence: 80%
“…4) with the possible occurrence either of a change in the slope or of a shoulder for 7 ≤ R G ≤10 kpc, as suggested by Twarog et al (1997); Caputo et al (2001), and Andrievsky et al (2004).…”
Section: The Iron Abundance Gradientmentioning
confidence: 90%
“…The metallicity is converted onto the Z scale using the relation; log Z = [Fe/H] − 1.7 (Fig. 5 of Caputo et al 2001 show this for LMC, SMC and Galactic Cepheids). Two sets of isochrones are produced; the first, younger set covers log (t/yr) = 9.1−9.4 with Z = 0.0125 and the second, older set covers log (t/yr) = 9.4−9.7 with Z = 0.0033 (log (t/yr) = 9.4 appears in both due to the SFH histogram bins overlapping).…”
Section: Reddening Valuesmentioning
confidence: 99%